The effects of job involvement and organizational trust on job satisfaction - Safdar, Hameed; Parveen, Kaur (Publications International Lahore, Pakistan, 2018)
Everybody knows that successful implementation of any strategic objective depends on the inspiration and hard work of the company employees. Researches indicate that satisfied employees are the major asset and source of any bank for successful achievement of its short-term and long-term objectives. The purpose of the current study was to examine the relationship between organizational trust and job involvement on employee job satisfaction among / Managerial / lower level employees in private banking sector of Pakistan. Organizational trust and job involvement were used as independent variables in the study while Job satisfaction was used as the dependent variable. Data was gathered from a random sample of 104 employees of the private banking sector of Lahore Pakistan. A questionnaire consisting of three parts was used for data collection. To gather biographical and occupational data, a self-designed 43-item questionnaire was used on 5-point scale Likert was used. Data analysis was done by means of various statistical techniques, including the Reliability Analysis Pearson Correlation Technique and Multiple Linear Regression Analysis. The results indicated that though both organizational trust and job involvement are strongly associated with job satisfaction, job involvement accounts for a higher proportion of variance in job satisfaction than organizational trust